2020
DOI: 10.3201/eid2612.203910
|View full text |Cite
|
Sign up to set email alerts
|

Flight-Associated Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 Corroborated by Whole-Genome Sequencing

Abstract: 19 had tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by PCR. All 6 passengers had disembarked from cruise ships that had recently docked in Sydney. In the subsequent 2 weeks, several other cases of SARS-CoV-2 infection were identified among passengers on that flight. Although the role of cruise ships in SARS-CoV-2 transmission is well documented (1), information regarding potential flight-associated transmission of SARS-CoV-2 (2,3) is limited. We investigated SARS-CoV-2 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 14 publications
2
82
0
Order By: Relevance
“…35 While IATA suggests that risk of in-cabin COVID-19 transmission is low 13 , COVID-19 has spread globally because of the movement of infected individuals by air travel. [9][10][11][12] Moreover, the IATA COVID-19 survey concluded that 36% of respondents would at least wait six months before considering traveling by air, with an additional 14% indicating they would not travel before a year or more from the moment the pandemic shows a true global decline and 5%…”
Section: Insert Figure 3 Herementioning
confidence: 99%
See 1 more Smart Citation
“…35 While IATA suggests that risk of in-cabin COVID-19 transmission is low 13 , COVID-19 has spread globally because of the movement of infected individuals by air travel. [9][10][11][12] Moreover, the IATA COVID-19 survey concluded that 36% of respondents would at least wait six months before considering traveling by air, with an additional 14% indicating they would not travel before a year or more from the moment the pandemic shows a true global decline and 5%…”
Section: Insert Figure 3 Herementioning
confidence: 99%
“…7 SARS-CoV-2 spread worldwide and was declared a global pandemic 8 in less than 3 months, driven principally by the movement of infected individuals by air. [9][10][11][12] The emergence of COVID-19 and its associated travel bans have reduced international passenger traffic. As of 8 October 2020, 1.2 billion passengers have travelled worldwide 13 , compared to the over 4.5 billion in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…6 were seated mid cabin and 5 aft cabin. They noticed a significantly greater risk of transmission in secondary infections in mid cabin vs aft cabin seats (11/112 vs 0/101 passengers) as well as window seats 7/28 vs non-window seats (4/83) [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, multiple cases have been identified associated with airplane travel, where social distancing is not feasible, including two flights prior to recommendations for universal masking where genomic sequencing was not performed, and a more recent publication identifying identical viral strains between two passengers and two flight staff with incubation periods suggesting exposure to staff during the flight ( 63 , 64 , 65 ). A contact investigation out of Australia identified 29 cases linked to a flight where mask use was infrequent with passengers from a known cruise ship outbreak resulting in multiple secondary cases identified by a distinct genetic cluster ( 66 ). Secondary cases were clustered in the mid cabin but were dispersed over nine rows ( 66 ).…”
Section: What Is the Value Of Masks For Rheumatic Disease Patients?mentioning
confidence: 99%
“…A contact investigation out of Australia identified 29 cases linked to a flight where mask use was infrequent with passengers from a known cruise ship outbreak resulting in multiple secondary cases identified by a distinct genetic cluster ( 66 ). Secondary cases were clustered in the mid cabin but were dispersed over nine rows ( 66 ).…”
Section: What Is the Value Of Masks For Rheumatic Disease Patients?mentioning
confidence: 99%